POTENSI KEBERHASILAN REHABILITASI HUTAN BERDASARKAN PERENCANAAN SECARA PARTISIPATIF DI PROVINSI LAMPUNG - Ahmad Khairil Fajri; wulandari, christine; Kaskoyo, Hari; Bakri, Samsul (Jurnal Belantara, 2024)
In forest management at the site level, involving local communities in Forest and Land Rehabilitation (RHL) activities is expected to have a real impact on the success and benefits of RHL activities. Community participation in RHL planning is carried out by giving the community the opportunity to directly choose the type, quantity and pattern of planting, determining the area and location of planting that will be used in RHL activities. This research aims to find out the reasons why farmers participate in the RHL program and whether the RHL planning pattern that accommodates the participation of the cultivating community can be well received and can increase the success of RHL. The determination of respondents was carried out using a random sampling technique with quota control, namely following information determined purposively so that 36 respondents were obtained, key information was selected based on role, knowledge, communicativeness and willingness to fill out interview questions. Data collection was carried out on September 21 2023, in the districts of West Lampung, East Lampung, South Lampung, Tanggamus, Pesawaran, Pesisir Barat, and Way Kanan. Data on farmers' opinions regarding participation in planning RHL activities collected was analyzed descriptively, while data on farmers' motivation to participate in RHL activities and sources of information on RHL activities were analyzed using regression (Regression Analysis). With community participation through selecting the type and determining the location of activities independently, it makes them confident to be involved in the implementation of RHL planning because with their participation the responsibility and success of RHL planting will increase. Furthermore, there is a relationship between farmers' information sources and motivation to participate in RHL activities. The availability of information will influence people's perceptions and motivation for RHL activities.